2016
DOI: 10.4054/demres.2016.34.19
|View full text |Cite
|
Sign up to set email alerts
|

Forgotten marriages? Measuring the reliability of marriage histories

Abstract: BACKGROUND Marriage histories are a valuable data source for investigating nuptiality. While researchers typically acknowledge the problems associated with their use, it is unknown to what extent these problems occur and how marriage analyses are affected. OBJECTIVE This paper seeks to investigate the quality of marriage histories by measuring levels of misreporting, examining the characteristics associated with misreporting, and assessing whether misreporting biases marriage indicators. METHODS Using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 61 publications
0
24
1
Order By: Relevance
“…Other studies that have followed young women in Malawi closely during the first years of their first union found even higher proportions, particularly in the south (Grant and Soler-Hampejsek 2014). The difference between these findings and our own are likely to reflect an underreporting by older women of early, very short marriages that are deemed unsuccessful (Chae 2016).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Other studies that have followed young women in Malawi closely during the first years of their first union found even higher proportions, particularly in the south (Grant and Soler-Hampejsek 2014). The difference between these findings and our own are likely to reflect an underreporting by older women of early, very short marriages that are deemed unsuccessful (Chae 2016).…”
Section: Discussioncontrasting
confidence: 57%
“…We restricted the analyses to women because men and women have different marital patterns and women tend to report on unions in more reliable ways than men (Chae 2016). We further limited our sample to respondents aged 50 and under, as older women are more likely to misreport early unions, especially if they were of short duration and were deemed unsuccessful (Reniers 2003).…”
Section: Quantitative Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that some men and women underreport marriages and divorces when asked to retrospectively report them in surveys (Chae 2016). This poses a potential problem because this study relies on women’s reports of marriages and divorces in retrospective marriage histories to determine whether a child’s parents are divorced.…”
Section: Datamentioning
confidence: 99%
“…To minimize this problem, I reconstructed marriage histories for women who were interviewed in 2006, 2008, and 2010. The algorithm used to reconstruct marriage histories is outlined elsewhere (Chae 2016). …”
Section: Datamentioning
confidence: 99%